Primary intraosseous Rosai Dorfman Disease: Case series with review of literature - Thomas, Amrutha; Ramamurthy, Sindhu; Rajasekaran, Raja Bhaskara; Thippeswamy, Pushpa Bhari (Journal of Pathology of Nepal, 2025)
Rosai-Dorfman disease (RDD) is a rare form of non-Langerhans cell histiocytosis of uncertain etiology, typically presenting as nodal lesions, with osseous involvement being uncommon. We retrospectively analyzed four intraosseous cases among 1,064 bone biopsies received between April 2023 and October 2024. All participants were young adults (mean age: 24 years), predominantly female, with solitary lytic lesions, most commonly located in the femur and tibia. Histology revealed histiocytes amidst lymphoplasmacytic infiltrates, neutrophils, and marrow fibrosis; emperipolesis was inconspicuous in two cases. Immunohistochemistry showed S100, CD68, CD163, and Cyclin D1 positivity; CD1a was negative. All patients underwent curettage (with or without bone grafting) and remained disease-free at follow-up. Rosai-Dorfman disease should be considered in young adults with lytic bone lesions; diagnosis requires careful histological and immunohistochemical evaluation.